2016
DOI: 10.1016/j.rmed.2016.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic challenges of bronchiectasis

Abstract: Bronchiectasis is a condition of increasing incidence and prevalence around the world.Many different diseases have been associated with bronchiectasis, and their treatment can differ widely. Recent guidelines have helped to approach aetiological diagnosis but it is still a complex process. Identifying the cause of the bronchiectasis may determine a change in the treatment of a large group of subjects. That is one of the main reasons why the aetiological diagnosis is crucial in the proper management of bronchie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…There are no guidelines to assess efficacy of eradication therapy, although studies of the impact of antibiotics in bronchiectasis have reported pathogen eradication at the end of clinical trials (where eradication was a secondary endpoint), at next clinic review, at 3 and 12 months of follow‐up and where no Pseudomonas was cultured in three sputum samples over 6 months after eradication . It would be pragmatic to assess sputum culture (at least once) at the next clinic appointment after antibiotics are completed and to assess regularly in the year following.…”
Section: Eradication Treatment In Bronchiectasismentioning
confidence: 99%
See 2 more Smart Citations
“…There are no guidelines to assess efficacy of eradication therapy, although studies of the impact of antibiotics in bronchiectasis have reported pathogen eradication at the end of clinical trials (where eradication was a secondary endpoint), at next clinic review, at 3 and 12 months of follow‐up and where no Pseudomonas was cultured in three sputum samples over 6 months after eradication . It would be pragmatic to assess sputum culture (at least once) at the next clinic appointment after antibiotics are completed and to assess regularly in the year following.…”
Section: Eradication Treatment In Bronchiectasismentioning
confidence: 99%
“…A recent study has evaluated the role of anti‐ P. aeruginosa IgG antibodies . Key results from this study demonstrated that a positive Pa‐IgG antibody test had high sensitivity (95%) and moderate specificity (74%) in patients with chronic P. aeruginosa infection.…”
Section: Eradication Treatment In Bronchiectasismentioning
confidence: 99%
See 1 more Smart Citation
“…Certainly there appears to be an underappreciated overlap in the pathogenic changes across bronchiectasis and COPD. In addition, bronchiectasis can also occur in patients in COPD and is associated with an increased risk of mortality and morbidity in moderate to severe COPD . Studies investigating patient subsets with bronchiectasis and COPD could reveal the link between specific microbial signatures and lymphoid neogenesis in the respiratory tract.…”
Section: Antigenic Triggers and Mechanisms That Induce Tlfs In Copdmentioning
confidence: 99%
“…Less frequent causes such as allergic bronchopulmonary aspergillosis, connective tissue disease, non-tuberculous mycobacterial disease and immunodeficiency must be identified and treated as they usually require a specific treatment not described below. (20)(21)(22)(23) Once the initial identification and treatment of underlying causes has been performed, the disease still presents individual "phenotypes". (24) Exacerbations of bronchiectasis typically presenting with a combination of increasing cough, sputum production, increasing sputum purulence, malaise, fever or worsening breathlessness.…”
Section: Exacerbations Of Bronchiectasismentioning
confidence: 99%